2019
DOI: 10.1038/s41598-019-41605-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs10830962 polymorphism with gestational diabetes mellitus risk in a Chinese population

Abstract: To date, only three polymorphisms (rs10830962, rs7754840 and rs1470579) are included in the genome-wide association study Catalog ( www.ebi.ac.uk/gwas ). However, the available evidence is limited in pregnant Chinese women. We aimed to explore the associations of three polymorphisms (rs10830962, rs7754840 and rs1470579) with GDM risk in a Chinese population. We conducted a case-control study (964 GDM cases and 1,021 controls) to evaluate the associations of these polymorphisms with GDM r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…The association of these genetic variants with GDM was also studied in a number of populations as this disease may have a common genetic background with T2DM [ 27 , 44 , 45 ]. Recently some studies on rs7756992 and rs7754840 reported significant association in Asian populations [ 26 , 28 , 46 , 47 ] whereas in some populations there was no association found [ 45 , 48 ]. Nevertheless, no report is available on the association of CDKAL1 rs7756992 and rs7754840 SNPs with GDM in Bangladeshi women.…”
Section: Discussionmentioning
confidence: 99%
“…The association of these genetic variants with GDM was also studied in a number of populations as this disease may have a common genetic background with T2DM [ 27 , 44 , 45 ]. Recently some studies on rs7756992 and rs7754840 reported significant association in Asian populations [ 26 , 28 , 46 , 47 ] whereas in some populations there was no association found [ 45 , 48 ]. Nevertheless, no report is available on the association of CDKAL1 rs7756992 and rs7754840 SNPs with GDM in Bangladeshi women.…”
Section: Discussionmentioning
confidence: 99%
“…To date, researchers investigated the association between three IGF2BP2 polymorphisms (rs4402960, rs1470579, rs11705701) and GDM. There was no evidence of the association between IGF2BP2 rs1470579 or rs11705701 and risk of GDM [9,10]. Recently, the association between IGF2BP2 rs4402960 polymorphism and risk of GDM has been discussed in many studies [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed in the pancreatic islets and plays a role in glucose homeostasis during pregnancy via the melatonin signaling pathway [ 74 ]. Three SNPs have been reported to be associated with elevated GDM risk (rs10830962, rs10830963, rs1387153) [ 37 , 38 , 49 , 51 , 52 ]. RS10830962 was associated with GDM in the Chinese population [ 51 ].…”
Section: Genomic Approaches Used In Understanding Gestational Diabetesmentioning
confidence: 99%
“…Three SNPs have been reported to be associated with elevated GDM risk (rs10830962, rs10830963, rs1387153) [ 37 , 38 , 49 , 51 , 52 ]. RS10830962 was associated with GDM in the Chinese population [ 51 ]. MTNRB1 polymorphism rs10830963 was found to be associated with GDM in Asians, Caucasians, and Arabs [ 36 , 38 , 49 , 52 ], while rs1387153 was a risk factor for GDM in Mexicans, Finnish, Danish, and Arab populations [ 36 , 37 , 38 , 49 ].…”
Section: Genomic Approaches Used In Understanding Gestational Diabetesmentioning
confidence: 99%